Learning Engagement of English Teacher (A Case Study at SMPN 33 Makassar) - Muh. Al Fairenza Arqam; Samtidar Samtidar; Amirullah Abduh (Journal of Excellence in English Language Education, 2023)
This study's objective is to determine the involvement of teachers in the learning process. This research uses qualitative research methods and is located at SMPN 33 Makassar. To achieve the research objectives, the data was collected in the form of a google form questionnaire, and interviews. There were 2 English teachers involved in this study, which also involved 104 seventh-grade students in different classes. The findings of this study suggest that teachers' involvement in English language instruction can be seen through the teacher setting clear learning goals, making the learning process comfortable, being creative with learning content, giving rewards to students who are actively involved in learning, and making open communication to good students. inside and outside the classroom. On the other hand, student involvement supports teacher involvement in the learning process. In light of the study's findings, it may be said that class VIII teachers at SMP Negeri 33 Makassar are always involved in learning English in class.